Robotic Complete Mesocolic Excision for Splenic Flexure of Colon Cancer. Issue 11 (November 2016) - Aghayeva, Afag; Baca, Bilgi; Atasoy, Deniz; Bayraktar, Onur; Ozben, Volkan; Erguner, Ilknur; Hamzaoglu, Ismail; Karahasanoglu, Tayfun
Abstract : Supplemental Digital Content is available in the text.